Developing global recommendations for action on climate change and mental health across sectors: A Delphi-style study - Justine Alford; Alessandro Massazza; Neil R Jennings; Emma Lawrance (Elsevier, 2023)
Introduction: Climate change is causing far-reaching yet underappreciated worsening of outcomes across the mental health and wellbeing spectrum. Despite increasing attention to the mental health impacts of climate change, an absence of a clear, cross-sectoral agenda for action has held back progress against the dual and interconnected challenges of supporting human and planetary health. This study aims to serve as an essential first step to address this gap. Methods: Harnessing the expertise of a diverse panel of 61 participants, representing 24 nationalities, this study developed and prioritized recommendations for action on climate change and mental health across the relevant sectors of research, policy, healthcare and the third sector, and used a Delphi-style methodology to examine their feasibility and importance. Results: Broadly, the prioritized recommendations highlighted the need to expand the evidence base, work collaboratively across sectors, and raise awareness. While broadly there was consensus on recommendation importance, there was greater variation in the reported feasibility of the recommendations, which differed across settings. Other common themes included the need for cultural and resource contextualization, raising awareness of and addressing mental health co-benefits via climate action, and working with communities with lived experience to develop and implement the findings. As there may be some interdependencies between the recommendations, further work needs to identify how best to implement them. Conclusion: The recommendations serve as a robust and evidence-based framework that can be used as a foundation to devise locally appropriate, concrete implementation strategies matching levels of need and resource. These also serve as a clear call to action for investment from leaders across sectors to ensure they are realized.